Similarities and differences between CLASS and ECERS-R estimates of educational environment quality - Bukhalenkova, Daria; Almazova, Olga; Aslanova, Margarita (Frontiers in Psychology, 2023)
The conducted research was devoted to comparison of kindergartens' educational environment quality evaluation via ECERS-R and CLASS methods. Both methods were applied in the same kindergarten groups. Therefore, in this study we attempted to find out if the the educational environment quality assessments acquired via the two methods mentioned above would coincide. We analyzed the results from the cultural-historical psychology perspective. The educational environment quality assessment has been conducted in 83 Moscow kindergarten groups where study 5 to7 years old preschoolers. The correlation analysis results show that the ECERS-R method subscales are not related to the "Emotional support" CLASS domain, however, a significant correlation with the total ECERS-R score has been revealed. The "Classroom Organization" CLASS domain has the highest number of correlations to the ECERS-R subscales (4) as well as to the total ECERS-R score. The "Instructional Support" domain is connected only to the Parents and Staff subscale within the ECERS-R method. As a result of comparing groups with relatively low and high quality of the educational environment, that were identified based on the evaluation via the ECERS-R and CLASS methods, a good agreement between the results has been revealed. However, a fairly large number of groups with high CLASS scores have made it to the pool of average-low ECERS-R scores, which demonstrates a non-linear connection between the educational environment quality evaluations according to these two methods. Research allows to conclude that the ECERS-R and CLASS approaches complement each other well.